Religion, Pluralism, and the Australian State after Same-Sex Marriage - Tregenza, Ian (A journal of church and state, 2024)
Since the passing of same-sex marriage legislation in 2017, religious freedom has become a prominent feature of Australian public debate. Overwhelmingly, such debates are conducted within a human rights framework where principles such as individual autonomy and protection from discrimination are prioritized over the communal and associational elements of religious life. This in turn tends to augment the power of the state vis-à-vis religious communities and institutions. In important respects, the dominance of human rights represents a new manifestation of the kind of "liberal-statism"—a public philosophy of liberal individualism that accepts the primacy of the state in the management of cultural and religious diversity—that has been a central feature of Australian religion-state relations over time. After some historical discussion of Australian church-state practice, this article argues for a reconsideration of a largely overlooked approach deriving from the English pluralists of the early twentieth century, which promoted greater degrees of group autonomy in relation to a rapidly growing state. It is argued that this tradition has greater potential in responding to the religious diversity of our time than does the current human rights approach with its tendency to reinforce an individualistic or privatized conception of religion, diminish associational life, and thereby reinforce state power.